Mule Deer A Handbook for Utah Hunters and Landowners - Austin, Dennis D. (University Press of Colorado, 2010)
A complete guide to the history, biology, hunting, and management of mule deer in Utah. The author, Dennis D. Austin, is a retired research scientist with more than thirty years of experience working as a wildlife biologist for the Utah Division of Wildlife Resources.